2023
DOI: 10.3390/ijms24076587
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Response of Cells in Neurogenic Niches to Neuronal Death: The Onset of Harmonic Repair?

Abstract: Harmonic mechanisms orchestrate neurogenesis in the healthy brain within specific neurogenic niches, which generate neurons from neural stem cells as a homeostatic mechanism. These newly generated neurons integrate into existing neuronal circuits to participate in different brain tasks. Despite the mechanisms that protect the mammalian brain, this organ is susceptible to many different types of damage that result in the loss of neuronal tissue and therefore in alterations in the functionality of the affected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 282 publications
0
6
0
Order By: Relevance
“…Brain injuries of different origins such as traumatic, ischemic or neurodegenerative stimulate neurogenesis in the SVZ resulting in a higher number of newly generated neuroblasts that attempt to migrate toward the injury [ 53 ] but do not reach the perilesional area [ 16 , 19 ] not contributing to neuronal replacement and to the regeneration of the injured region. Failure of neuroblasts to migrate toward the injury has been reported to be a consequence of the presence or absence of signaling molecules that affect neuroblast migration [ 33 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain injuries of different origins such as traumatic, ischemic or neurodegenerative stimulate neurogenesis in the SVZ resulting in a higher number of newly generated neuroblasts that attempt to migrate toward the injury [ 53 ] but do not reach the perilesional area [ 16 , 19 ] not contributing to neuronal replacement and to the regeneration of the injured region. Failure of neuroblasts to migrate toward the injury has been reported to be a consequence of the presence or absence of signaling molecules that affect neuroblast migration [ 33 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…NSCs can expand long basal processes that envelop the vessels by expressing laminins and integrins typical of the SVZ [ 146 ]. In addition, vasculature is related to the migration of NSCs and its progeny, serving as support scaffolds [ 31 , 147 ]. Related to this microenvironment close to the sanguine vessels, non-neurogenic functions can be attributed to NSCs, but taking into account neuromodulatory and neuroprotective functions.…”
Section: Neurogenesis In the Subventricular Zonementioning
confidence: 99%
“…In addition, OB neurogenesis in mice has been described as an additional process throughout life [ 149 , 150 ], whereas, in adult humans, researchers were unable to find neurogenesis in the OB, nor the addition of new neuroblasts generated from the SVZ to the OB [ 2 , 151 ]. However, neuroblasts from the SVZ can migrate to other brain regions in the human brain, such as the basal ganglia and the cerebral cortex, mostly under pathological conditions [ 31 , 39 , 152 ].…”
Section: Neurogenesis In the Subventricular Zonementioning
confidence: 99%
See 1 more Smart Citation
“…The potential proliferation of precursor stem cells provides the mature brain with flexibility and self-renewal through neurogenesis, which occurs in response to external stimuli and damage [97,98]. It has been shown that in the ischemia-tolerant brain, the proliferation of precursor cells increases after focal ischemia and preconditioning [99,100].…”
Section: Proliferative and Synthetic Activitymentioning
confidence: 99%